The role of cardiac biomarkers as predictors of trastuzumab cardiotoxicity in patients with breast cancer - Ürün, Y.; Utkan, G.; Yalcin, B.; Akbulut, H.; Onur, H.; Oztuna, D.G.; Şenler, F.Ç.; Demirkazık, A.; İçli, F. (Experimental Oncology, 2015)
Aim: Identification of patient with increased risk of cardiotoxicity would allow not only prevention and early diagnosis of chemotherapy related cardiotoxicity but also administration of optimal dose and duration of chemotherapy. Materials and methods: Fifty-two women with HER2+ breast cancer treated with trastuzumab were included in this study. Patients were prospectively followed with routine cardiac evaluation. Before and after administration of trastuzumab blood samples for NT-proBNP were also taken. Results: The median age was 48.5 year (range: 26–74). Hypertension and obesity were two most common co-morbidities. The median duration application of trastuzumab was 52 weeks. During median 14.5 (3–33) months follow-up cardiac adverse events occurred in 5 (9.6%) patients and 2 out of 5 was grade III–IV heart failure. Both patients had preserved left ventricular ejection fraction and no symptom of heart failure before trastuzumab but older than 65 years old and had diabetes mellitus and obesity. High level of NT-proBNP (> 300 ng/ml) was observed in both patients and heart failure recovery was not observed. There was statistically significant difference regarding body mass index (p = 0.004) and diabetes mellitus (p = 0.002) between patients with and without cardiotoxicity. Conclusion: Although, cardiac biomarkers still cannot replace routine cardiac monitoring, natriuretic peptides may provide additional tool for detection of patients with high risk of cardiotoxicity and early detection of cardiotoxicity. Key Words: breast cancer, trastuzumab, heart failure, left ventricular dysfunction, natriuretic peptides.